Regionalismen - Engel, Ulf (Dialektik des Globalen, 2018)
Regions have been widely expressed in the sovereignty strategies of concrete actors since the early 19th century; Since the end of the Cold War, they seem to be a favored response to current globalization processes, especially in the Global South. This volume introduces the fragmented knowledge of different disciplines on the topic of regions and regionalization projects.